Sam68 regulates cell proliferation and cell adhesion‐mediated drug resistance (CAM‐DR) via the AKT pathway in non‐Hodgkin's lymphoma. (19th October 2015) - Wu, Yaxun; Xu, Xiaohong; Miao, Xiaobing; Zhu, Xinghua; Yin, Haibing; He, Yunhua; Li, Chunsun; Liu, Yushan; Chen, Yali; Lu, Xiaoyun; Wang, Yuchan; He, Song
Abstract: Objectives: Sam68 (Src‐associated in mitosis 68 kDa), a substrate for tyrosine kinase c‐Src during mitosis, is up‐regulated in a variety of human cancers and acts oncogenically promoting tumour progression. This study has explored biological function and clinical significance of Sam68 in non‐Hodgkin's lymphoma (NHL). Materials and methods: To examine Sam68 expression in NHL, clinically, eight diffuse large B‐cell lymphomas and four reactive lymphoid hyperplasia fresh‐frozen tissues were obtained for western blot and quantitative real‐time PCR analyses. Using immunohistochemical staining, paraffin wax embedded sections from 164 cases of NHL patients were used to evaluate prognostic value of Sam68. Cell Counting Kit‐8 (CCK‐8) and soft agar colony assays were conducted to investigate the role of Sam68 in cell viability and cell proliferation respectively. Furthermore, effects of Sam68 on cell adhesion‐mediated drug resistance (CAM‐DR) was determined by CCK‐8 assay and flow cytometric analysis. Results: Expression status of Sam68 inversely correlated with clinical outcomes of patients with NHL, and it was also an independent prognostic factor for the outcomes. In addition, Sam68 was associated with proliferation of NHL cells. Knock‐down of its gene inhibited cell proliferation and colony formation by delaying cell cycle progression. Furthermore, OCI‐Ly8 and Jeko‐1 cells adhering to FN and HS‐5 expressed higher Sam68 protein, compared to their suspension counterparts. Sam68 promoted cell adhesion‐mediated drug resistance (CAM‐DR) via the AKT pathway. Conclusions: Increased Sam68 expression in NHL resulted in poor prognosis, and it promoted CAM‐DR in NHL via AKT.